1996
DOI: 10.1207/s15516709cog2004_1
|View full text |Cite
|
Sign up to set email alerts
|

Shuttling Between Depictive Models and Abstract Rules: Induction and Fallback

Abstract: When reasoning about physical systems, people sometimes experience the phenomenology of depicting the system's behavior in their imagination (Clement, 1994;disessa, 1993;Hegarty, 1992). Because people do not experience this phenomenology throughout their reasoning, we assume that its onset reflects a functional shift in problem solving strategies. Beginning with this assumption, we consider why and when people use imagistic models to reason about a physical system, and how this imagery becomes related to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 46 publications
9
189
1
3
Order By: Relevance
“…Such mental simulations may tap tacit or implicit knowledge about physical constraints such as object constancy, solidity, or inertia that may be present early in life. Schwartz and Black [56] argued that people may fall back on imagistic mental models in situations where they do not have adequate explicit knowledge. However, although implicit knowledge may be activated during mental simulation, it may not be consciously accessible or open to reflection.…”
Section: Common Mechanism?mentioning
confidence: 99%
“…Such mental simulations may tap tacit or implicit knowledge about physical constraints such as object constancy, solidity, or inertia that may be present early in life. Schwartz and Black [56] argued that people may fall back on imagistic mental models in situations where they do not have adequate explicit knowledge. However, although implicit knowledge may be activated during mental simulation, it may not be consciously accessible or open to reflection.…”
Section: Common Mechanism?mentioning
confidence: 99%
“…Gesture could, for example, draw attention to unhelpful features of the problem. Schwartz and Black (1996) found that adults who were allowed to gesture while solving gear problems used a strategy in which they modeled the movement of each individual gear, often in their gestures. In contrast, adults who were prevented from gesturing generated rule-based strategies, which are a more efficient way of solving the gear task (Alibali, Spencer & Kita, 2004, as described in Alibali, 2005.…”
Section: How General Is Gesture's Effect On Learning?mentioning
confidence: 99%
“…Gesturing also provides kinaesthetic and visual feedback that can directly aid problem-solving. People can use gesture to work through different solutions to a problem and gather information about the alternatives through the visual and motor feedback of their own gestures [36].…”
Section: Gesture and Thoughtmentioning
confidence: 99%